Natural building stone in the construction and renovation of the Zagreb Cathedral (Rudarsko-geološko-naftni zbornik, 2023)
Natural stone has been used since the dawn of civilization as a construction material for buildings that are historical and cultural buildings and monuments. The Zagreb Cathedral is an example of such a historical and cultural building and data regarding the extraction of stone for its construction and reconstruction is scientifically underestimated. Based on a review of previously published literature and an investigation on the current state of the sites where stone for construction was previously quarried, this paper presents a systematic overview of challenges regarding stone material that will be faced in the restoration of the Cathedral after the 2020 earthquakes. The autochthonous stone varieties used for the Cathedral, namely lithothamnium limestone, litavac, calcareous sandstone, and vinicite were determined. The description of the locations where they were quarried was emphasized, and the suitability of these sites for re-quarrying the stone blocks during reconstruction after the 2020 earthquake was investigated. In addition, the Cathedral was renovated in the meantime with travertine imported from Italy, which, although it is not of domestic origin, represents an integral part of the Cathedral and whose characteristics must be taken into account in the planning of the current reconstruction of the Cathedral. To preserve the cultural memory of quarrying in the Zagreb area, emphasis is given to the importance of preserving and showing old visual representations of the quarries.